Inter-Relationship Between a Transcriptional Regulator of Flagella Genes cj0440c and Thiamine Metabolic Pathway in Campylobacter jejuni. (21st August 2022) - Shabbir, Muhammad Abu Bakr; Ul-Rahman, Aziz; Khalid, Abdur Rauf; Ijaz, Nabeel; Aleem, Muhammmad Tahir; Ahmed, Saeed; Alouffi, Abdulaziz; Ahmed, Waqas; Aslam, Faiza; Maan, Muhammad Kashif; Tahir, Adnan Hassan; Aziz, Muhammad Waqar; et al.
Abstract : Campylobacter jejuni is a major cause of gastroenteritis in humans. It has been reported that the pathogenesis of C. jejuni is closely related to the formation, adhesion, and invasion of flagella toxin in host epithelial cells. A putative transcriptional regulator, known as cj0440c, is thought to be involved in the regulation of flagellar synthesis. However, confirmation of this hypothesis requires deep insight into the regulation mechanism of cj0440c and its possible relationship with different antibiotics. Therefore, the study explained here was designed to determine the relationship and function (phenotypically and genotypically) of cj0440c in the flagellar synthesis of C. jejuni NCTC11168. The study determined the mode of expression of cj0440c and flagella-related genes under exposure to various drugs. To verify the involvement of cj0440c protein in the metabolic pathway of thiamine, an enzymatic hydrolysis experiment was performed and analyzed through the application of mass spectrometry. The overexpression vector of C. jejuni NCTC11168 was also constructed to find out whether or not target genes were regulated by cj0440c . The findings of the study showed that cj0440c and other flagella-related genes were expressed differentially under the influence of various antibiotics including erythromycin, tylosin, azithromycin, gentamicin, etimicin, enrofloxacin, gatifloxacin, tetracycline, and tigecycline. The analysis showed that the cj0440c protein did not catalyze the degradation of thiamine. In conclusion, the study aids in the understanding of the inter-relationship between the regulatory mechanism of flagella genes and the thiamine metabolic pathway.